Heritage, second and third language learner processing of written corrective feedback: Evidence from think-alouds - Bowles , Melissa A.; Gastañaga , Kacie (Studies in Second Language Learning and Teaching, 2022)
This study compares the processing of three different types of written corrective feedback (WCF) by heritage language (HL), second language (L2), and third language (L3) learners who wrote and revised three short essays and received a different type of WCF for each essay (i.e., direct, coding, or underlining). Comparison of pre- and post-feedback texts and analysis of think-alouds served as the basis for determining whether one type of feedback promoted higher depth of processing (DoP) and whether this processing was mediated by error type and language background. The findings indicate that feedback type did interact with DoP, and that this interaction was in some ways mediated by learner background and error type. This research serves as a first step toward understanding how these three learner groups are impacted by these commonly used feedback types and is therefore important to drive evidence-based pedagogical decisions.